Investigation of the role of tyrosine kinase receptor EPHA3 in colorectal cancer - Andretta, Elena (Sci Rep, 2017)
EPH signaling deregulation has been shown to be important for colorectal carcinogenesis and genome-wide sequencing efforts have identified EPHA3 as one of the most frequently mutated genes in these tumors. However, the role of EPHA3 in colorectal cancer has not been thoroughly investigated. We show here that ectopic expression of wild type EPHA3 in colon cancer cells did not affect their growth, motility/invasion or metastatic potential in vivo. Moreover, overexpression of mutant EPHA3 or deletion of the endogenous mutant EPHA3 in colon cancer cells did not affect their growth or motility. EPHA3 inactivation in mice did not initiate the tumorigenic process in their intestine, and had no effects on tumor size/multiplicity after tumor initiation either genetically or pharmacologically. In addition, immunohistochemical analysis of EPHA3 tumor levels did not reveal associations with survival or clinicopathological features of colorectal cancer patients. In conclusion, we show that EPHA3 does not play a major role in colorectal tumorigenesis. These results significantly contribute to our understanding of the role of EPH signaling during colorectal carcinogenesis, and highlighting the need for detailed functional studies to confirm the relevance of putative cancer driver genes identified in sequencing efforts of the cancer genome.